Long‐read genome sequencing resolves a complex 13q structural variant associated with syndromic anophthalmia. Issue 5 (5th February 2022) - Boerkoel, Pierre K.; Dixon, Katherine; Fitzsimons, Carrie; Shen, Yaoqing; Huynh, Stephanie; Schlade‐Bartusiak, Kamilla; Culibrk, Luka; Chan, Simon; Boerkoel, Cornelius F.; Jones, Steven J. M.; Chin, Hui‐Lin
Abstract: Microphthalmia, anophthalmia, and coloboma (MAC) are a heterogeneous spectrum of anomalous eye development and degeneration with genetic and environmental etiologies. Structural and copy number variants of chromosome 13 have been implicated in MAC; however, the specific loci involved in disease pathogenesis have not been well‐defined. Herein we report a newborn with syndromic degenerative anophthalmia and a complex de novo rearrangement of chromosome 13q. Long‐read genome sequencing improved the resolution and clinical interpretation of a duplication–triplication/inversion–duplication (DUP‐TRP/INV‐DUP) and terminal deletion. Sequence features at the breakpoint junctions suggested microhomology‐mediated break‐induced replication (MMBIR) of the maternal chromosome as the origin. Comparing this rearrangement to previously reported copy number alterations in 13q, we refine a putative dosage‐sensitive critical region for MAC that might provide new insights into its molecular etiology.